PENTA HELIX AS STRATEGY OF TOURISM VILLAGE DEVELOPMENT IN KARANGASEM VILLAGE, BULU DISTRICT, SUKOHARJO REGENCY - Ratna Susanti; Suci Purwandari; Basnendar Herry Prilosadoso (Bajang Institute, 2022)
This study aims to identify the integration of tourism development in Karangasem Village using the penta helix, which is a process of synergy between the five helices to support tourism in Karangasem Village. The five helics are academics, business, communities, media, and government. This study uses a qualitative descriptive method by applying the data collection techniques of Miles, Huberman, and Saldana, namely data condensation, data display, and drawing conclusions. The results of this study indicate that each stakeholder has their role in the development of a tourism village. The academics focus on training and mentoring for Pokdarwis members as well as tourism village managers regarding tourism village management and promotion strategies, the business sectors focus on increasing value and maintaining economic growth in the Karangasem tourism village, the community help to support and manage the tourism potential, the media help to publish news on tourism village branding as well as promotion, and the governments collaborate with academics to make policies of the management of tourism villages. The collaboration between the various actors involved government, community, business sector, academics and mass media can provide positive feedback in the concept of developing a tourism village in Karangasem Village.